Makna Ungkapan 'Meup on Ate, Het Bukae on Usif': Analisis Filsafat Bahasa Hermeneutik Hans-Georg Gadamer terhadap Bahasa Dawan (Uab Meto) - Amon Bernabas Tenis (Perspektif, 2026)
Language functions not only as a means of communication but also as a medium for transmitting values, worldviews, and collective wisdom within a community. One such example is the traditional Dawan expression “Meop on ate henati, bukae on usif,” which embodies values of work ethic, humility, and social honor. However, the philosophical meaning of this expression is often understood normatively and has rarely been examined through the lens of philosophical hermeneutics. This study addresses the problem of how the expression can be interpreted from Hans-Georg Gadamer’s hermeneutic perspective and what philosophical values it represents as an expression of the Dawan people’s way of life. This research aims to interpret the meaning of “Meop on ate henati, bukae on usif” and to reveal its philosophical and cultural significance. This study employs a qualitative approach using Gadamer’s philosophical hermeneutic method, involving textual analysis of the cultural expression, in-depth interviews with traditional leaders and native speakers, and observation of its socio-cultural usage. The findings indicate that the expression constitutes a living cultural text containing an ontological dimension of language, reflecting work ethic as a path to honor and prosperity, and functioning as a medium of moral education and intergenerational transmission of values within Dawan society.